If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(-5+x)=2(5-x)
We move all terms to the left:
2(-5+x)-(2(5-x))=0
We add all the numbers together, and all the variables
2(x-5)-(2(-1x+5))=0
We multiply parentheses
2x-(2(-1x+5))-10=0
We calculate terms in parentheses: -(2(-1x+5)), so:We get rid of parentheses
2(-1x+5)
We multiply parentheses
-2x+10
Back to the equation:
-(-2x+10)
2x+2x-10-10=0
We add all the numbers together, and all the variables
4x-20=0
We move all terms containing x to the left, all other terms to the right
4x=20
x=20/4
x=5
| 6x+4x=3x+6 | | 12b=6b-6 | | -7-18x=-27x+2 | | 4d+2=(d-1)(d-3) | | 2(104+3x)=-3x+28 | | 2(-27-x)=5(-6-x) | | 7n^2-22n-24=0 | | 1.5^(x-1)=14.5 | | 0.5x^2+x+2=0 | | -3(-2-7k)=153 | | 2(-27-x)=6(-6-x) | | ℎ= | | 9+5x+17-10x=10x+35 | | 3p-p=8 | | 12(21-x)=6(-3x+28) | | 7x=0.21 | | 1.8x=4x-32 | | 8w-12=-4(w+6) | | 2(72+x)=3(-x+28) | | 2n+16=-5n+51 | | 2n+16=-5n+51* | | -8(1+3n)=-176 | | 5(-4+3x)=-100 | | 3x-3+2x=x+2 | | 49-5x=34 | | x*9,600=12 | | 44=8x-20 | | 100000=5x+x | | z*7/9=3 | | 5x-18=x-4 | | (6x-1)(6x+1)-4x(9x+3)=-4 | | 67x+24=22 |